Qualitative gender analysis country report, Zambia: Building equitable climate resilient African bean and insect sectors - Mulube, Mwiinga; Banda, Arnold; Chanda, Moses; Ouya, Frederick; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (2025)
This report presents findings from a qualitative gender analysis conducted under the Building Equitable Climate Resilient African Bean and Insect Sectors (BRAINS) project in Zambia. The study was implemented in seven districts across six provinces—Eastern, Central, Lusaka, Northern, Muchinga, and Luapula to establish a baseline understanding of climate resilience, gender dynamics, and farmers’ socio-economic opportunities within three value chains of fruit trees, common beans, and bees/insects for feed and food. The study adopted a qualitative design involving 47 Focus Group Discussions (FGDs) of men-only, women only, and mixed groups; 60 Key Informant Interviews (KIIs); and in-depth interviews with farmers, entrepreneurs, persons living with disabilities, and other marginalised groups. The data was analysed thematically to explore gender roles, decision-making patterns, livelihood diversification, waste management, and access to finance and collective networks. Results show differences in gender roles across the common bean, insect, and fruit tree value chains in the different provinces. For instance, in the bean value chain, men, women, and youths participate in most activities, with women more involved in planting, winnowing, sorting, and selling while men transport the beans to the market. Women mostly sold beans at the farm gate, while men sold in higher-value markets. In fruit tree production, land preparation and planting were mainly done by men. Both men and women did the weeding and mulching. However, men do most of the harvesting and hand over the fruits to women to sort and proceed to sell. Transportation and marketing were done by men and women, depending on the volumes harvested. Insect harvesting was seasonal and done mainly by women. Overall, men made most decisions, except for divorced women and women-headed households. Climate variability poses substantial challenges for all farmers and entrepreneurs across different value chains. Droughts, heavy rains, and pest infestations significantly reduced yields and caused income losses. Despite these challenges, farmers in Zambia are increasingly adopting various climate-resilient practices, such as intercropping, early planting, crop rotation, planting early-maturing varieties, and agroforestry, to manage the effects of climate change, including delayed rainfall, droughts, pest outbreaks, and soil degradation, which have significantly reduced yields and incomes. Waste management practices varied from composting and animal feeding to burning of residues, with limited awareness of sustainable methods. Financial services such as credit remained largely inaccessible due to high interest rates and rigid repayment terms. At the same time, social networks and farmers’ cooperatives played a key role in disseminating agricultural knowledge and supporting adaptation. The study concludes that gender and social inequalities continue to influence decision-making, access to resources, and resilience to climate change. Women, youth, and people living with disabilities face deepened barriers to climate-smart technologies, financial services, and market participation. The report recommends targeted capacity-building on gender-responsive climate-smart practices for the three value chains, facilitation of inclusive financial mechanisms, and strengthening of social networks to enhance equitable resilience and sustainable livelihoods.